Pengaruh Independensi, Skeptisme, Pengalaman Kerja, dan Fee Audit Terhadap Pendeteksian Kecurangan: Studi Empiris di Wilayah Jakarta Pusat - Arief, Rachmat; Pakpahan, Marojahan Martin Andreas (PT Hakhara Akademia Indonesia, 2024)
This study aims to analyze the influence of independence, skepticism, work experience, and audit fees on fraud detection. The data used in this study is primary data in the form of data obtained directly from the original source (without intermediaries) which was selected based on the method of distributing questionnaires on predetermined samples. The population used in this study were auditors who worked in public accounting firms (KAP) located in the Central Jakarta area. Based on the results of research that has been carried out, it was obtained that independence has a significant effect on fraud detection, the results of skepticism research have a significant effect on fraud detection, the results of work experience research do not have a significant effect on fraud detection, fee audit research results have a significant effect on fraud detection.